Meeting the medieval in a digital world - Davis, Matthew Evan; Mahoney-Steel, Tamsyn, 1978-; Turnator, Ece (Leeds : Arc Humanities Press, 2018)
This book looks at the intersection between medieval studies and digital humanities, confronting how medievalists negotiate the 'virtual divide' between the cultural artefacts that they study and the digital means by which they address those artefacts. The essays come from medievalists who have created digital resources or applied digital tools and methodologies in their scholarship. Text encoding and analysis, data modeling and provenance, and 3D design are all discussed as they apply to western European medieval literature, history, art history, and architecture.
Statistical analysis and the boundaries of the genre of Old English Prayer / William H. Smith and Charles L. Butler -- If (not "Quantize, Click, and Conclude") Digital methods in Medieval studies, Katayoun Torabi -- Project paradise: a geo-temporal exhibit of the Hereford Map and The Book of John Mandeville / Alexandra Bolintineau -- Ghastly vignettes : Pierce the Plowman's Crede : the ghost of Shakespeare's Blackfriars, and the future of the digital past / Jim Knowles -- Content in context : radical transparency and the acknowledgement of informational palimpsests in online display / Matthew Evan Davis -- Encoding and decoding Machaut / Tamsyn Mahoney-Steel -- Of dinosaurs and dwarves : moving on from Mouvance in digital editions / Timothy L. Stinson -- Adam Scriveyn in cyberspace : loss, labour, ideology, and infrastructure in interoperable reuse of digital manuscript metadata / Bridget Whearty -- Digital representations of the provenance of Medieval manuscripts / Toby Burrows -- Bridging the gap : managing a digital Medieval initiative across disciplines and institutions / Joseph Koivisto, Lilla Kop©Łr, and Nancy L. Wicker.
Title from publisher's bibliographic system (viewed on 08 Feb 2021).
Keywords: Digital humanities; Middle Ages -- Historiography; Middle Ages -- Research -- Electronic information resources; Middle Ages -- Study and teaching -- Methodology